2016
DOI: 10.3389/fphar.2016.00070
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Efficacy and Safety of Compound Kushen Injection Combined with Transarterial Chemoembolization in Unresectable Hepatocellular Carcinoma: An Update Systematic Review and Meta-Analysis

Abstract: Background: Compound Kushen Injection (CKI) is a Chinese patent medicine approved by the China Food and Drug Administration for the treatment of various types of solid tumors. CKI, combined with transarterial chemoembolization (TACE), is believed to increase the therapeutic efficacy of unresectable hepatocellular carcinoma (HCC). We report an updated and extended meta-analysis with detailed outcomes of both the efficacy and adverse events (AEs) of CKI combined with TACE therapy.Materials and methods: Electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…17 The application of CKI for the treatment of a variety of cancer types has also been studied in breast cancer, 19 colon cancer, 20 nonsmall cell lung cancer, 21 acute leukemia, 22 and HCC. [23][24][25] Sorafenib, the first frontline drug, has been widely used for advanced HCC therapy for a long time. However, only on July 17, 2020 by guest.…”
Section: Cki Sensitizes Hcc To the Therapeutic Effects Of Subclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The application of CKI for the treatment of a variety of cancer types has also been studied in breast cancer, 19 colon cancer, 20 nonsmall cell lung cancer, 21 acute leukemia, 22 and HCC. [23][24][25] Sorafenib, the first frontline drug, has been widely used for advanced HCC therapy for a long time. However, only on July 17, 2020 by guest.…”
Section: Cki Sensitizes Hcc To the Therapeutic Effects Of Subclinicalmentioning
confidence: 99%
“…17 21 22 For HCC, CKI increases the therapeutic efficacy of TACE against unresectable liver cancer. [23][24][25] However, the effect of CKI on tumor immunity and its underlying mechanism remain poorly understood. Particularly, considering the different modes of action of immunotherapeutic (microenvironment-targeted) and chemotherapeutic drugs (tumor cell-targeted), it is necessary to illustrate the potential efficacy of combined treatment with CKI and chemotherapeutic drugs against HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its very poor prognosis resulting from metastasis and recurrence, it has been regarded as the third most common cause of death from cancers worldwide1. In the past decades, several new treatment options have been developed and recommended for patients with HCC2345. Among these treatments, the transarterial chemoembolization (TACE) is reported to be an effective treatment for advanced-stage HCC patients, especially for those cases with 3- to 5-cm tumors56.…”
mentioning
confidence: 99%
“…It is widely used as an adjuvant medicine in the treatment of carcinomas for pain relief, activation of innate immune response and reduced side effects in cancer therapy 12,13 . Our previous results have shown that CKI suppresses the growth of cancer cells by inhibiting cell cycle, energy metabolism, and DNA repair pathways 11,14 .…”
Section: Introductionmentioning
confidence: 99%